Performance of simplified methods for quantification of [18F]NaF uptake in fibrodysplasia ossificans progressiva - de Ruiter, Ruben Daniel; Botman, Esmée; Teunissen, Bernd P.; Lammertsma, Adriaan Anthonius; Boellaard, Ronald; Raijmakers, Pieter G.; Schwarte, Lothar A.; Nieuwenhuijzen, Jakko A.; Gonzalez Trotter, Dinko; Eekhoff, Elisabeth Marelise W.; Yaqub, Maqsood (Frontiers in Nuclear Medicine, 2024)
Background: Fibrodysplasia Ossificans Progressiva (FOP) is a rare, genetic disease in which heterotopic bone is formed in muscles, tendons and ligaments throughout the body. Disease progression is variable over time and between individuals. 18 F-fluoride uptake in newly formed bone can be evaluated using [ 18 F]NaF (ie. sodiumfluoride) PET/CT, identifying active areas of bone formation in FOP. The purpose of this study was to assess the performance of various semi-quantitative methods with full kinetic analysis. Results: Seven patients (age range: 20 -31 years) with FOP underwent dynamic [ 18 F]NaF scans at baseline and after one year. [ 18 F]NaF uptake was measured in aorta descendens, vertebrae, heterotopic bone lesions and metabolically active regions on PET, and quantified using nonlinear regression (NLR) analysis together with standardized uptake value (SUV) and target-to-blood ratio (TBR). SUV was on measured the 40 -45 minutes frame of the dynamic sequence (SUV 40-45 ) and on the subsequent static sweep (SUV Static ). Correlations between and SUV 40-45 and NLR-derived Ki were comparable when normalized to body weight (r = 0.81, 95% CI 0.64 -0.90), lean body mass (r = 0.79, 95% CI 0.61 -0.89) and body surface area (r = 0.84, 95% CI 0.70 -0.92). Correlation between TBR 40-45 and NLR-derived Ki (r = 0.92, 95% CI 0.85 -0.96) was higher than for SUV 40-45 . Correlation between TBR 40-45 and NLR-derived Ki was similar at baseline and after one year (r = 0.93 and 0.94). The change in TBR 40-45 between baseline measurement and after one year correlated best with the change in NLRderived Ki in the PET-active lesions (r=0.87). Conclusion: The present data supports the use of TBR for assessing fluoride uptake in PET-active lesions in FOP.